O processo de elaboração do luto e as respostas ocupacionais no cotidiano de mães enlutadas - Dahdah, Daniel Ferreira (2019)
INTRODUCTION: Bereavement is a process that occurs with the loss, by death, of a significant person. This is a painful experience that leads to the need to adapt to the new situation. Maternal bereavement becomes peculiar because it reverses the expected cycle of life, generating feelings of guilt and shame, accompanied by grief and the feeling of having failed in the role of mother. Occupations change during the bereaved process, as their constituent elements - doing, being, becoming and belonging – are affected, causing a crisis in maternal daily life. AIM: To understand the bereaved mothers’ occupations in their everyday life. METHOD: A cross-sectional, exploratory and qualitative study that used the Oral History technique, in the biographical narrative modality. The inclusion of the participants came from a group of mutual aid and selection, by the “snowball” technique. Ten mothers are included in the study. The data were generated from three collection instruments: field diary, timeline, and semi-structured interview. The results were categorized and analyzed by content analysis using deductive and inductive methods. RESULTS: In the field diary, the main topics addressed in the mutual help group were recorded. The timeline allowed us to visualize the “birthday reactions” and to identify, chronologically, the mothers' experience during the dates associated with bereavement. From the interviews, six categories emerged: The notification of the death of the son; The experience of motherhood before and after the death of the son; The meanings constructed by mothers after the death of their son; The future; Religiosity and spirituality helping to coping with bereavement; and, Occupational responses in the face of changes imposed on the everyday lives of bereaved mothers after the death of their sons. From the results, it was possible to systematize the occupational responses in the daily lives of bereaved mothers. DISCUSSION: Triangulation was used as a methodological strategy to broaden the understanding of the studied phenomenon. Identified that mothers perceived their personal and spiritual growth, found meaning and benefits in loss, did the changes in identity necessary to continue life. Also, they regain familiarity with their surroundings and was able to live authentically in everyday lives, enabling them to felt happy again. The results reaffirmed the bereavement process as a singular and individual experience, however, intensely permeated by social aspects, and mainly related to social and emotional support for coping with the bereavement. The study contributed to the understanding of the process of adaptation to bereavement through the occupational responses in maternal everyday life. Thus, depending on the form, purpose, and meaning of the occupational responses presented after to the death of the son, it was possible to categorize them into adaptive strategies that help the mother to adapt occupationally in everyday life. Besides, they support the reconstruction of meanings in response to bereavement and changes in everyday life and occupations. They also allow revisions about themselves, about desires, priorities, and the continuity of life in the world profoundly modified by the reality of the son's death. CONCLUSION: The occupational therapist, by identifying the elements of the bereavement adaptation process, assists the mothers in the reconstruction of the occupational meanings, in the encounter with the familiarity of the environment and in the accomplishment of the necessary changes for the continuity of life, repositioning in practical and emotional terms the absence of the deceased son in everyday life.